Shepherd’s Crook deformity with neck of femur fracture in fibrous dysplasia treated with valgus osteotomy, fibular strut graft and fixation with proximal femur locking plate – A Case Report. (Journal of Pakistan Orthopaedic Association, 2020)
Fibrous dysplasia is a rare developmental abnormality of bone formation. The clinical presentation varies from asymptomatic disease to gross deformity and disability. Proximal femur bowing and coxa vara(Shepherd’s Crook deformity) is frequently noted in polyostotic fibrous dysplasia. For treating Shepherd’s Crook deformity but We treated our patient in a single stage surgery with valgus osteotomy, fibular strut grafting and proximal femur locking plate. At one year follow up she had excellent functional outcome. Our case report highlighted three important principles of managing fibrous dysplasia with pathological fracture neck of femur. Firstly, fixation of the fracture and accelerating bone healing with a fibular strut graft. Secondly, simultaneous restoration of the mechanical axis by correcting the deformity with valgus osteotomy. Thirdly, total hip replacement will be technically easy without needing further corrective surgery if the patient subsequently develops osteoarthritis or avascular necrosis of the femur head in future.